2021
DOI: 10.1111/jcmm.16599
|View full text |Cite
|
Sign up to set email alerts
|

Qianliexin capsule exerts anti‐inflammatory activity in chronic non‐bacterial prostatitis and benign prostatic hyperplasia via NF‐κB and inflammasome

Abstract: Qianliexin capsule (QLX) is a standardized traditional Chinese herbal preparation that has long been used to treat chronic non‐bacterial prostatitis (CNP) and benign prostatic hyperplasia (BPH). This study investigated the anti‐inflammatory activity of QLX in improving lower urinary tract symptoms (LUTS) associated with CNP and BPH. Rat models of CNP and BPH were induced by oestradiol or testosterone (hormonal imbalance) or chemical inflammation (carrageenan). QLX significantly relieved LUTS in CNP and BPH rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The autophagy in prostate epithelial cells could be induced by the reduced secretion of IGF-1 from prostatic stromal cells after the treatment with finasteride [35]. Several herbal extracts, including Stauntonia hexaphylla and Qianliexin capsule, a standardized traditional Chinese herbal preparation, have been reported to induce autophagy and apoptosis in BPH in vivo [11,36]. In this study, we found that RWF extract could induce autophagic genes, ULK2 and SQSTM1/p62 at the transcriptional level in both BPH-1 and WPMY-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy in prostate epithelial cells could be induced by the reduced secretion of IGF-1 from prostatic stromal cells after the treatment with finasteride [35]. Several herbal extracts, including Stauntonia hexaphylla and Qianliexin capsule, a standardized traditional Chinese herbal preparation, have been reported to induce autophagy and apoptosis in BPH in vivo [11,36]. In this study, we found that RWF extract could induce autophagic genes, ULK2 and SQSTM1/p62 at the transcriptional level in both BPH-1 and WPMY-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB signaling pathway, which seemed to be the imperative convergence of proinflammatory factors, has gradually become a research hotspot of BPA-triggered toxicity [ 48 , 49 ]. In the human prostatic epithelium, the inflammasome component NLRP3 activation controlled by NF-κB and ROS modulation could provoke the release of a series of proinflammatory factors and initiate an inflammatory cascade [ 50 ]. The BPA- and BPAF-driven ascended expression of and COX-2 in rat VP, as well as in human prostate cells, demonstrated that both of them hold promise as the potential interlocutors in mediating the prostatic hyperplasia disrupted by BPA and BPAF.…”
Section: Discussionmentioning
confidence: 99%
“…While in the experimental autoimmune prostatitis (EAP) mouse model, apart from the attenuating effect of the NLRP3 inhibitor MCC950 ( 67 ), melatonin also inhibited the NLRP3 inflammasome signaling pathway by activating Sirt1, which reduced prostate inflammation and pelvic pain ( 68 ). Zang et al found elevated expression of NLRP3, Caspase-1 and ASC in CNP rats, and Qianliexin capsule (QLX) suppressed the high expression of these proteins ( 69 ). Another study showed that the levels of Caspase-1 and Pyrin domain containing proteins 1 and 3 (NALP1 and NALP3) were increased in local carrageenan-induced prostate inflammation ( 70 ).…”
Section: Pyroptosis In Prostate Diseasementioning
confidence: 99%